Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
2x - 3y = -12 ⇒ 2x - 3y = -12⇒ 2x - 3y = -12
x + y = 1 ⇒ 2(x + y) = 1⇒ 2x + 2y = 1
y = -11
2x - 3y = -12
2x - 3(-11) = -12
2x + 33 = -12
- 33 - 33
2x = -45
2x = -45
2 2
x = -22.5
(x, y) = (-22.5 , -11)
x + y = 1 ⇒ 2(x + y) = 1⇒ 2x + 2y = 1
y = -11
2x - 3y = -12
2x - 3(-11) = -12
2x + 33 = -12
- 33 - 33
2x = -45
2x = -45
2 2
x = -22.5
(x, y) = (-22.5 , -11)
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.